Deubiquitylases MoUbp12 and MoUbp14 modulated by transcription factor MoMsn2 are critical for mitochondrial fusion/fission balance and infectious growth of the rice blast fungus - Xingyu Wang; Yuhan Xiao; Qi Li; Lele Xu; Yayuan Huang; Muxing Liu; Xinyu Liu; Zhengguang Zhang; Haifeng Zhang (Phytopathology Research)
Abstract Ubiquitination is a critical post-translational modification that regulates various cellular processes, including protein degradation and organelle dynamics. In particular, it plays a significant role in modulating mitochondrial fission and fusion, which are essential for maintaining cellular energy balance and function. In our previous study, we reported the transcription factor (TF) MoMsn2 plays a critical role in regulating mitochondrial morphology and invasive growth of the rice blast fungus Magnaporthe oryzae. Here, we further identified two target genes of MoMsn2, MoUBP12 and MoUBP14, which encodes deubiquitinating enzymes (DUBs) that involved in mitochondrial dynamics and invasive growth. Our results revealed that MoMsn2 positively regulates the transcription levels of MoUBP12 and MoUBP14. Deletion of MoUBP12 or MoUBP14 resulted in excessive mitochondrial fusion or fission, respectively, which were associated with reduced invasive growth, decreased mitochondrial membrane potential (MMP), and increased ubiquitination levels. Importantly, overexpression of MoUBP12 in the ΔMoubp14 mutant efficiently reduced its ubiquitination level, with restored mitochondrial fusion and virulence, while overexpression of MoUBP14 in the ΔMoubp12 mutant failed to rescue the defects. Overall, our data demonstrate that ubiquitination level mediated by DUBs MoUbp12 and MoUbp14 is important for mitochondrial morphology maintenance and invasive growth of the rice blast fungus.